CHEMICAL COMPOSITION AND MEDICINAL PROPERTIES OF WATERMELON FRUIT (Scientific journal of the Fergana State University, 2023)
The article provides information about the chemical composition and healing properties of watermelon fruit. The norms of daily consumption of watermelon fruit and how much of it can replenish the necessary substances for the body are given. It is also possible to use not only the inside of the watermelon for consumption, but also the peel part and seeds of the watermelon. Watermelon has more vitamins, dietary fiber, alkaloids and macro-and micronutrients than the inside of the peel and seeds. This article provides information on the use of watermelon waste in folk medicine in the treatment and prevention of diseases.